CORPORATE SOCIAL RESPONSIBILITY STRATEGIC IMPLEMENTATION IN FOREIGN MARKET: GLOBAL VS. LOCAL POLICY - Diskienė, Danuta; Krapchilo, Daria (Ekonomika, 2012)
Corporate social responsibility (CSR), understood as a concept of socially responsible business behaviour, is becoming one of the important and actual business practices. Globally more and more MNEs are engaging themselves into CSR activities and see CSR as part of their corporate strategy. This paper presents an analysis of existing CSR strategic options for international companies to choose, and reveals what influences international companies’ decision what strategy and instruments to choose for implementing in a host country or market. In particular, the implementation of CSR strategic options and instruments in Belarus are analysed. The concept of this paper is based on the integration of a theoretical idea and business management practices. Since the object of the research is complex, it required the application of different research methods, such as theory analysis, system analysis, meta-analysis, survey, content-analysis, and expert interview methods. The findings of the study could be useful for foreign companies deciding to enter the Belarusian market, make M&A with local companies, for local managers responsible for CSR at their company, as well for researchers interested in CSR implementation in Eastern Europe.